PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP - Novia, Silva (Departemen Matematika, 2023)
The ability to solve mathematical problems in learning is a basic thing that students should have. According to test results from SMPN 1 Hulu Kuantan, students had poor problem-solving abilities, receiving an average of 11.4% on each indicator. Students' mathematical problem-solving skills do not develop adequately due to a lack of active participation in the learning process and the approach used. Realistic mathematics education (RME) is a possible method of instruction. This study aims to assess and describe how well students learn to solve mathematical problems using the RME methodology, which is superior to learning through conventional methods. This kind of study uses a nonequivalent posttest-only control group design and a quasi-experimental methodology. The entire class of students in grade 8 at SMPN 1 Hulu Kuantan. According to the results of the data description and analysis, students at SMPN 1 Hulu Kuantan who study using the RME technique have more advanced mathematical problem-solving skills than students who learn using conventional methods.Keywords – RME, Mathematical Problem Solving